2009
DOI: 10.1007/s10517-009-0710-0
|View full text |Cite
|
Sign up to set email alerts
|

Endostatin, Placental Growth Factor, and Fibroblast Growth Factors-1 and -2 in the Sera of Patients with Primary Osteosarcomas

Abstract: Serum levels of endostatin, placental growth factor (PlGF), and fibroblast growth factors-1 and -2 (FGF-1 and FGF-2) were measured in 58 patients with primary osteosarcomas before therapy and in 21 healthy subjects. The incidence of serum FGF-1 in bone tumors was 2.5 times higher than in healthy individuals (p=0.004); significant levels of FGF-2, PlGF, and endostatin were detected in all examined subjects. The mean serum level of endostatin in healthy individuals was significantly lower than in the total group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
2
4
0
1
Order By: Relevance
“…In our series, the largest so far conducted in this setting, VEGF levels had no significant impact on outcome, in agreement with Rutkowski et al [25]. As in previous studies of bFGF [13, 25], we found no clinical value of this angiogenic factor in osteosarcoma. Here, as in the study by Rastogi et al [23], serum VEGF levels fell significantly between baseline and surgery, with a slightly larger variation in patients who had a good histologic response.…”
Section: Discussionsupporting
confidence: 93%
“…In our series, the largest so far conducted in this setting, VEGF levels had no significant impact on outcome, in agreement with Rutkowski et al [25]. As in previous studies of bFGF [13, 25], we found no clinical value of this angiogenic factor in osteosarcoma. Here, as in the study by Rastogi et al [23], serum VEGF levels fell significantly between baseline and surgery, with a slightly larger variation in patients who had a good histologic response.…”
Section: Discussionsupporting
confidence: 93%
“…Placenta growth factor (PIGF) is a dimeric glycoprotein with structural and functional similarities to VEGF [75]. PIGF serves a function in tumor angiogenesis [76][77][78]. Previous studies indicated that overexpression of PIGF had a close relation with early recurrence of HCC [79,80], and our finding showed PIGF had higher serum levels in HCC, suggested that PIGF may be a prognostic indicator and a diagnostic biomarker of HCC.…”
Section: Discussionsupporting
confidence: 61%
“…Mice overexpressing FGF23 display increased expression of Runx2 and alkaline phosphatase, receptor activator of NFκB ligand or RANKL and osteoprotegerin transcripts, MMP9 and cathepsin K immunoexpression along with increased serum concentrations of C terminal telopeptide of collagen (CTX) with increased bone resorptive activity [61]. Vitamin D mediated down regulation of FGF1 in OS cells is significant as previous studies have detected increased levels of serum FGF1 and FGFR1 amplification in OS patients [62,63]. FGF1 mediated activation of PKA and PKC signaling pathways induces nucleoside triphosphate pyrophosphohydrolase (NTPPPH) expression in OS cells [64].…”
Section: Discussionmentioning
confidence: 99%